TRANSFORMASI PENGEMBANGAN KURIKULUM DALAM MENGHADAPI PERUBAHAN SOSIAL DAN TEKNOLOGI - Iqlil Khoerul Ma’mun; Rifa Qotrun Nada; Salsabila, Nandya Ayu; Muhammad Rizky Saputra; Ma’mun Hanif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid social and technological developments of the modern era have brought significant changes to the world of education, particularly in curriculum development. This study aims to examine how the curriculum can continuously adapt to remain relevant to the needs of the times. Changes in lifestyle, social values, and the demands of modern society are important factors influencing the direction and content of the curriculum. On the other hand, technological advances also open up new opportunities in the learning process, both in the form of media, methods, and learning resources that are more varied and interactive. Using a qualitative approach, this study examines various literature and phenomena occurring in the world of education. The results of the study indicate that the integration of 21st-century skills, such as critical thinking, creativity, collaboration, and communication, is crucial in shaping students who are ready to face future challenges. Furthermore, curriculum implementation also needs to be designed adaptively and flexibly to keep up with the rapid changes of the times. Transformation of curriculum development is no longer an option, but rather a necessity that must be implemented continuously. A curriculum that is responsive to social and technological changes will help create a more relevant, effective education system and be able to prepare a generation ready to face global dynamics.